Household leverage and labor market outcomes: Evidence from a macroprudential mortgage restriction - Gazi Kabaş; Kasper Roszbach (Norges Bank, 2021)
Does household leverage matter for worker job search, matching in the labor market, and wages? Theoretically, household leverage can have opposing effects on the labor market through debt-overhang and liquidity constraint channels. To test which channel dominates empirically, we exploit the introduction of a loan-to-value ratio restriction in Norway that exogenously reduces household leverage. Focusing on a sample of displaced workers who bought a house before losing their jobs due to mass layoffs, we find that a reduction in leverage raises the subsequent wages of these workers. Lower leverage enables workers to search longer, find jobs in higher-paying firms, and switch into new occupations and industries. The positive effect on wages is persistent and more pronounced for young and highly-educated workers who are more likely to benefit from the effects of a reduction in leverage on job search. Our results indicate that in addition to reducing financial stability risks, policies limiting household leverage can improve workers' labor market outcomes.
hdl:11250/2833887
Keywords: E21; G21; G51; J21; 330; Household Leverage; Household Debt; Job Displacement; Job Search; Macroprudential Policy